Analysis of activity structure in Szabolcs-Szatmár-Bereg County - I. Takács; V. E. Mazák; A. Fenyvesi; R. Bársony; E. Topa (Brazilian Journal of Biology, 2024)
Abstract Agriculture has become multifunctional, its task is no longer only the production of healthy food, but it has also expanded with the functions of regional development, landscape management, environmental protection and tourism. This research seeks to explore the multifaceted nature of agriculture, extending beyond traditional food production, by investigating the interconnectedness of various functions, including energy conversion, utilization, and job creation, within the cohesive framework of rural development. According to another claim, agriculture cannot solve the problems of employment and job creation, but at the same time, it forms an economic basis for the quality of the cultural environment. Food production, energy conversion, use, and job creation systems form the unified structure of rural development. Their properties and characteristics, which are embodied in projects, can be interpreted in a system. This way of thinking prevails and strengthens even more when we examine spatial environments adjacent to borders since the connecting role and nature of development processes can be demonstrated for different social, economic and natural environments and its validity can be examined in adaptive solutions.